The above equation can be written as
"(2y^3x^2dx+x^3y^2dy)-(5ydx+7xdy)=0"
Reforming the equation as
"(y^3x^2dx+x^3y^2dy+y^3x^2dx)-(5ydx+7xdy)=0"
Multiplying and dividing by 3
"\\frac{1}{3}(3y^3x^2dx+3x^3y^2dy)+y^3x^2dx-(5ydx+7xdy)=0"
Let total differential be "x^3y^3"
the "d(x^3y^3)=3x^2y^3dx+3y^2x^3dy"
"\\frac{1}{3}d(x^3y^3)+x^2y^3dx-(5ydx+7xdy)=0"
"\\frac{1}{3}d(x^3y^3)+x^2y^3dx-(5ydx+5xdy+2xdy)=0"
"\\frac{1}{3}d(x^3y^3)+x^2y^3dx-5(ydx+xdy)-2xdy=0"
Lets select the total differential be xy then,
"d(xy)=xdy+ydx"
"\\frac{1}{3}d(x^3y^3)+x^2y^3dx-5d(xy)-2xdy=0"
Consider the equation
"x^2y^3dx-2xdy=0"
Above equation can be written as,
"\\int xdx=\\int\\frac{2}{y^3}dy"
Integrate both th sides
"\\frac{x^2}{2}=-\\frac{1}{y^2}+c"
Where c i a constant
Hence the overall solution of given equation is,
"\\frac{x^3y^3}{3}-5xy+\\frac{x^2}{2}+\\frac{1}{y^2}=c"
Comments
Leave a comment